Pancreatitis as a Main Consequence of APOC2-Related Hypertriglyceridemia: The Role of Nonsense and Frameshift Variants - Bahareh Rabbani; Mohadeseh Aghli Moghadam; Shiva Esmaeili; Amirhassan Rabbani; Bahman Akbari; Nejat Mahdieh (International Journal of Genomics)
APOC2-related hypertriglyceridemia occurs due to biallelic variants of this gene. Here, genotype-phenotype architecture of all pathogenic APOC2 variants is investigated among heterozygous and homozygous individuals. Clinical heterogeneity of various types of the variants is also described, and pancreatitis in more than half of homozygotes carrying chain-termination variants is highlighted as well. For this study, patients were selected who had a plasma triglyceride level above 250 mg/dL. The coding and intronic regions of the APOC2 gene were amplified using the Sanger sequencing to investigate the presence of variants. The genotypes, lipid profiles, and detailed clinical features were documented for all APOC2-related patients and heterozygous individuals. Pathogenicity of the variants was predicted and categorized using available bioinformatics tools such as MutationTaster and PolyPhen-2 and ACMG criteria. MetaDome and Phyre2 were applied for structural and functional in silico analyses. 40% (12 out of 30) of APOC2 variants were chain-termination (nonsense and frameshift) variants. These types of variants were determined in 60.53% of patients. 55% of these patients showed pancreatitis followed by lipemia retinalis (29%), abdominal pain (24%), hepatosplenomegaly (24%), and xanthomas (18%). The mean age of onset was about 22 years old. In at least 50% of 38 homozygous individuals, the TG level was more than 2000 mg/dL. More than 25% of heterozygous individuals showed at least one symptom. Pancreatitis and a severe form of HTG were found in 5 and 2% of heterozygous individuals, respectively. The main clinical features of APOC2-related hypertriglyceridemia include pancreatitis, lipemia retinalis, abdominal pain, hepatosplenomegaly, and xanthomas. Nonsense and frameshift homozygous variants usually lead to a severe form of hypertriglyceridemia. Pancreatitis is one of the main consequences of these types of mutations; thus, it is important to consider this point when evaluating asymptomatic individuals. Heterozygous individuals may become symptomatic due to the role of unknown modifying agent including environmental genetic factors.